2000
DOI: 10.1021/bi0022644
|View full text |Cite
|
Sign up to set email alerts
|

NMR Evidence for a Short, Strong Hydrogen Bond at the Active Site of a Cholinesterase

Abstract: Cholinesterases (ChE), use a Glu-His-Ser catalytic triad to enhance the nucleophilicity of the catalytic serine. It has been shown that serine proteases, which employ an Asp-His-Ser catalytic triad for optimal catalytic efficiency, decrease the hydrogen bonding distance between the Asp-His pair to form a short, strong hydrogen bond (SSHB) upon binding mechanism-based inhibitors, which form tetrahedral Ser-adducts, analogous to the tetrahedral intermediates in catalysis, or at low pH when the histidine is proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 26 publications
4
71
0
2
Order By: Relevance
“…As shown in Fig. 5, there is no signal in the 13-22-ppm range in the absence of a (45)(46)(47)50). Besides the two strong hydrogen bonds of the triad, there are two additional short hydrogen bonds between the SHCHC ligand and the side chains of Arg 90 and Ser 86 in the MenH-SHCHC structure that are 2.66 and 2.56 Å, respectively.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…As shown in Fig. 5, there is no signal in the 13-22-ppm range in the absence of a (45)(46)(47)50). Besides the two strong hydrogen bonds of the triad, there are two additional short hydrogen bonds between the SHCHC ligand and the side chains of Arg 90 and Ser 86 in the MenH-SHCHC structure that are 2.66 and 2.56 Å, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…When these enzymes interact with their mechanism-based inhibitors, the imidazole ring in the side chain of the central histidine is protonated, and its hydrogen bond with the acidic residue is greatly strengthened, leading to a significant downfield shift of the corresponding proton signal into the 16 -19.5-ppm range (45)(46)(47). Based on these facts, we used NMR spectroscopy to detect the proton in the strong hydrogen bond between the side chains of Asp 201 and His 232 in the catalytic triad of 15 N-labeled MenH.…”
Section: Resultsmentioning
confidence: 99%
“…23 The results of the present study raise concern about assignment of downfield NMR peaks solely based on sitedirected mutagenesis experiments or by simple comparison with serine proteases, which is commonly adopted by others. 24,25,32,33 Even among serine proteases, it has been reported that the prolyl oligopeptidase family exhibits important dissimilarities in the active site compared to the pancreatic and subtilisin classes of serine proteases. 34 In the case of the prolyl oligopeptidase, non-catalytic histidine imidazole ring-attached protons are engaged in relatively strong hydrogen bonds based on the observation that their downfield chemical shifts are virtually independent of pH up to pH 9.5.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of SSHBs has so far been reported for a considerable number of enzymes, including ketosteroid isomerase (15)(16)(17), triosephosphate isomerase (18), serine proteases (3,6,19), tryptophan synthase (20), 2-amino-3-ketobutyrateCoA ligase (21), and cholinesterases (22,23). Their occurrence has typically been suggested by NMR spectroscopy (24,25).…”
mentioning
confidence: 99%